Randomized Controlled Trial Comparing Outcomes of Video Capsule Endoscopy with Push Enteroscopy in Obscure Gastrointestinal Bleeding - Dev S Segarajasingam; Stephen C Hanley; Alan N Barkun; Kevin A Waschke; Pascal Burtin; Josée Parent; Serge Mayrand; Carlo A Fallone; Gilles Jobin; Ernest G Seidman; Myriam Martel (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Optimal management of obscure gastrointestinal bleeding (OGIB) remains unclear.